RANCANG BANGUN SISTEM KONTROL DAN MONITORING BEBAN LISTRIK PADA UNIT PRODUKSI BAKMI GM DENPASAR DENGAN INTERNET OF THINK MENGGUNAKAN APP INVENTOR - I wayan dikse Pancane; Ahmad Aslih Syani Abu Zahir (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Electricity is a primary human need today. Because nowadays all equipment is electronic-based, it allows the use of large amounts of power every day. It can be seen clearly that every year the use of electricity is increasing. An example that we can see the development of the times at this time, so many restaurants are emerging. Each restaurant requires a large amount of electrical power for their production equipment. With the need for large electrical power, a tool is also needed to be able to monitor the power. One of the advances that can be felt is in the field of control, currently with the network technology, computers can be solved, especially those based on the internet / IOT (Internet Off Things) which have grown rapidly making the problem of distance and time barriers can be solved solution and time. The interface used for operation is App Invetor, which system-wise, App Inventor consists of two components, namely the server and the client. The App Inventor server functions to store all program assets and provide other services related to application (project) file management.